Learning a second language through interaction - Ellis, Rod.; Fotos, Sandra (Amsterdam ; Philadelphia : J. Benjamins, 1999)
This book examines different theoretical perspectives on the role that interaction plays in second language acquisition. The principal perspectives are those afforded by the Interaction Hypothesis, Socio-Cultural Theory and the Levels of Processing model. Interaction is, therefore, defined broadly; it is seen as involving both intermental and intramental activity. The theoretical perspectives are explored empirically in a series of studies which investigate the relationship between aspects of interaction and second language acquisition. A number of these studies consider the effects of interac.
LEARNING A SECOND LANGUAGE THROUGH INTERACTION; Editorial page; Title page; LCC data; Table of Contents; Acknowledgments; Preface; SECTION 1. Introduction; SECTION 2. Input, Interaction and Vocabulary Learning; SECTION 3. Interaction and Grammar Learning; SECTION 4. Pedagogical Perspectives; SECTION 5. Conclusion; References; Index.
Includes bibliographical references (pages 259-280) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Second language acquisition; Interaction analysis in education; Langue seconde -- Acquisition; Interaction en éducation.; Interaction analysis in education; Second language acquisition; Diskursanalyse; Fremdsprachenlernen; Tweedetaalverwerving; Interactie; Taalonderwijs; Electronic book